The Tinderbox - Book 1 - Lewis, Beverly 1949- (Bloomington, Minnesota : Bethany House Publishers, 2019)
"When Sylvia Miller finds the key to an old tinderbox of her fathers, her curiosity is piqued. Shocked by the secrets it holds, Sylvia confronts her father. The truth about the tinderbox will forever change not only her own life, but also that of her family and her Amish community" --
Keywords: Amish; Fiction; Family secrets; Fiction; Religious fiction